Trace Element Accumulation in Common Kestrel Falco tinnunculus Collected from Haneda Area, Japan in 1999 - WATANABE, Izumi; IWAMIZU, Yoshikazu; KUNO, Katsuji; HORAI, Sawako; HIRAOKA, Takashi; MOTOMURA, Ken; TANABE, Shinsuke (Journal of Environmental Chemistry, 2003)
Trace element concentrations (Li, Na, Mg, Al, K, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Se, Rb, Sr, Ag, Cd, Cs, Ba, Hg, Tl, Bi and U) in the liver, kidney, pectoral muscle and lung of common kestrels (Falco tinnunculus) collected from Haneda area, Japan in 1999 were determined, in order to elucidate the properties of accumulation and the distribution in the body. Although Mn in the liver was higher than those in other three tissues, almost all elements analyzed were higher in the kidneys and lungs. The elements (Co, Ni, Cu, Zn, Cd, Tl and Bi) were higher in the kidney than in the liver. Concentrations of Al, V Ga, Ba, Bi were higher in the lungs as compared with other organs. It was suggested that this distribution was related to air pollution. Cr levels decreased in analyzed all tissues with aging. V levels decreased in kidney, liver and pectoral muscle with aging. Ni concentrations increased in liver and lung whereas they decreased in kidney and pectoral muscle with aging. For sexual differences, while concentrations of Al, Ca, V Co, Ga, Se, Rb, Sr, Cs, Ba and Tl were higher in male than in female, the levels of Mn, Ag, Cd, Bi and U were higher in female than in male. Inter-element relationships between Ca, Zn, Sr, Cs, Bi and U concentrations in the kidney, Mn, Co, Cs, Tl, Bi and U concentrations in the liver, and Li, Mg, Al, Ca, V, Mn, Ga, Sr, Ba, Tl, Bi and U concentrations in the lung were significant (p<0.001, by Speareman's rank correlation) . Values of V Mn, Cs and Tl in the liver and kidney were higher in this species than in other several raptors.